Max Weber e o problema da dialética: presença do idealismo na formação dos tipos ideais - Roselino, Luis F. de Salles (2010)
This work has the dialectics as its main theme and aims to present Max Weber s thought before the legacy of German idealism, i.e., by the particular way that Hegel (as much as Marxism) has defined dialectics in history. Dialectics will be investigated inside Max Weber s historical typologies as a product of history and reason together. We serve ourselves of two histories of philosophy, that of the Windelband and of Lukács, and from those two perspectives our object is approached by a philosophical as well as a historical and sociological perspective. Thus, we shall observe how the uses of Weber s types are immerged inside the same limits and philosophical legacy of Kant and Hegel.